Marine Toxins That Target Voltage-gated Sodium Channels - Al-Sabi, Ahmed (Molecular Diversity Preservation International (MDPI), 2006)
Eukaryotic, voltage-gated sodium (Na(V)) channels are large membrane proteins which underlie generation and propagation of rapid electrical signals in nerve, muscle and heart. Nine different Na(V) receptor sites, for natural ligands and/or drugs, have been identified, based on functional analyses and site-directed mutagenesis. In the marine ecosystem, numerous toxins have evolved to disrupt Na(V) channel function, either by inhibition of current flow through the channels, or by modifying the activation and inactivation gating processes by which the channels open and close. These toxins function in their native environment as offensive or defensive weapons in prey capture or deterrence of predators. In composition, they range from organic molecules of varying size and complexity to peptides consisting of ~10–70 amino acids. We review the variety of known Na(V)-targeted marine toxins, outlining, where known, their sites of interaction with the channel protein and their functional effects. In a number of cases, these natural ligands have the potential applications as drugs in clinical settings, or as models for drug development.